The m5C methyltransferase NSUN2 promotes progression of acute myeloid leukemia by regulating serine metabolism - Songyu Li; Ya Liu; Xiang Wu; Minjia Pan; Hongxia Zhao; Yunguang Hong; Qinghua Zhang; Shushu Hu; Aorong Ouyang; Guangru Li; Minhui Wu; Shanshan Fan; et al. (Cell Reports)
Summary: Acute myeloid leukemia (AML) is one of the most prevalent heterogeneous hematologic malignancies with a complicated etiology. RNA post-transcriptional modifications have been linked to the incidence and progression of AML, while the detailed mechanism remains to be elucidated. In this study, we find that NOP2/Sun domain family member 2 (NSUN2), a methyltransferase of 5-methylcytosine (m5C) RNA methylation, is upregulated in AML and predicts a poor prognosis for patients with AML. Knockdown of NSUN2 in AML cells inhibits proliferation and colony formation and promotes apoptosis. Depletion of NSUN2 in AML mice reduces the tumor burden and prolongs survival. Mechanistically, NSUN2 promotes the expression of phosphoglycerate dehydrogenase (PHGDH) and serine hydroxymethyltransferase 2 (SHMT2), two key enzymes in the serine/glycine biosynthesis pathway, by stabilizing the corresponding mRNAs through regulation of m5C modifications. Overall, our findings demonstrate a critical role of NSUN2 in AML development and highlight the therapeutic potential of targeting the NSUN2/m5C axis for the treatment of this cancer.